1992
DOI: 10.3354/meps082075
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and seasonal variation of NH4+pools in differert typos of coastal marine sediments

Abstract: Seasonal variations in pools of porewater NH,' and exchangeable NH,+ desorbed by l-step [easily desorbed NH,') and multiple KC1 extractions (tightly bound NH,') were investigated in sediments from 3 stations in Danish coastal waters. One-step KC1 extractions gave higher yields in winter and lower yields in periods of increased sediment activity and temperature. The exchangeable NH,' pool obtained by l-step extraction was always less than the total pool removed by the multiextraction technique, independent of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Since the mat cores did not contain enough extractable liquid for direct centrifugation, 5 ml of synthetic seawater, free of nitrate or nitrite, was added to each tube, homogenized and centrifuged for 10 min at 10 000 × g. Nitrite and nitrate concentrations were analyzed with a Technicon-Auto-Analyser according to Treguer & Le Corre (1975). Ammonium concentration was determined after KCl extraction (Laima 1992) using the phenol/hypochlorite method (Koroleff 1969). These values were corrected for dilution and addition of reagent. )…”
Section: Methodsmentioning
confidence: 99%
“…Since the mat cores did not contain enough extractable liquid for direct centrifugation, 5 ml of synthetic seawater, free of nitrate or nitrite, was added to each tube, homogenized and centrifuged for 10 min at 10 000 × g. Nitrite and nitrate concentrations were analyzed with a Technicon-Auto-Analyser according to Treguer & Le Corre (1975). Ammonium concentration was determined after KCl extraction (Laima 1992) using the phenol/hypochlorite method (Koroleff 1969). These values were corrected for dilution and addition of reagent. )…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the production of 29 N 2 continued to the end of the trial (12 h), being sustained by the NO 2 Ϫ pool, which remained largely untouched until after 8 h, when the concentration of NO 3 Ϫ had been reduced to approximately 200 M. The rates of turnover were consistently equal for NO 3 Ϫ and NO 2 Ϫ , being equivalent to 0.11 and 0.12 mol ml of wet sediment Ϫ1 h Ϫ1 , respectively, at a starting concentration of 800 M. Anaerobic ammonium oxidation produced 0. 16 (Fig. 4a).…”
Section: Methodsmentioning
confidence: 99%
“…Blackburn (1980) made a seasonal study of ammonium, in a n anoxic marine sediment, which showed th.at ammonium production was closely related to the temperature cycle. Laima (1992) also found in his study of Danish coastal sediments that temperature variations had a pronounced effect on the production rate of ammonium. Otherwise, there seems to be a lack of studies of seasonality in marine sediments and how mineralization rates, adsorption processes and transport processes of amino acids and ammonium are affected by seasonal changes of e.g.…”
Section: Introductionmentioning
confidence: 91%
“…Microbial activity in coastal marine sediments at most sites in the temperate zone is generally regulated by seasonal changes of input of organic matter, bottom water temperature and oxygen concentration. Laima (1992) did a seasonal study of Danish coastal sediments, which were highly influenced by seasonal changes in temperature and organic matter input, and found that even the tightly bound pool of ammonium in the sediment (shaken several times with potassium chloride) varied seasonally.…”
Section: Adsorption Coefficientsmentioning
confidence: 99%